The genetic regulation of Kranz anatomy in maize - Hughes, T (2016)
The C4 photosynthetic pathway acts to concentrate CO2 around the enzyme Ribulose-1,5-bisphosphate carboxylase oxygenase (Rubisco), ensuring that it catalyses a carboxylation rather than oxygenation reaction, which in turn suppresses photorespiration. In nearly all cases C4 photosynthesis is underpinned by characteristic Kranz anatomy, with concentric wreaths of bundle sheath (BS) and mesophyll (M) cells surrounding closely spaced veins. The increased yields associated with the C4 pathway have lead to the suggestion that C3 crops such as rice should be engineered to undertake C4 photosynthesis, however, this goal is currently held back by a lack of understanding about how the development of Kranz anatomy is regulated. Recently, a number of candidate Kranz regulators have been identified in an RNA-seq study that compared leaf development in maize foliar (Kranz) and husk (non-Kranz) leaves. However, this study did not consider the impact of a recent whole genome duplication in the maize lineage on the gene expression patterns analysed. Therefore, in this thesis maize homeolog gene-pair divergence during early leaf development was assessed. This revealed that expression divergence of homeolog gene-pairs is a significant evolutionary phenomenon. Functional validation of a subset of Kranz candidates revealed that a Zmscr1-1; Zmscr1h-1 double mutant exhibited defects in Kranz patterning, including increased formation of extra BS cells and veins with no separating M cells. Furthermore, Zmnkd1; Zmnkd2 double mutants exhibited a subtle increase in extra BS cell formation. Taken together, this indicates that both ZmSCR1/ZmSCR1h and ZmNKD1/ZmNKD2 function redundantly during Kranz development. No evidence was obtained that two additional genes, ZmSHR2 and ZmRVN1, play a role in Kranz development, and expression of candidate Kranz regulators in rice did not alter leaf anatomy. Together, this work has confirmed roles for a number of genes in Kranz regulation, and has provided insight into the complex regulation underpinning Kranz development in maize.